Tinjauan Atas Prosedur Pemeriksaan Pendapatan Harian Food And Beverage Pada Aston Bogor Hotel & Resort - Salsabil, Nafizhan; Amrulloh, Amrulloh (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
Food and Beverage sales as one of the largest income generators do not rule out the possibility of human error or fraud which could result in the truth or authenticity of the revenue being generated not being known. So the role of Income Audit as an examiner of daily food and beverage income is really needed. The purpose of writing this final assignment is to find out the procedure for checking daily food and beverage income by Income Audit, to find out what the procedure is for monitoring the use of Restaurant Bills and Captain Order Slips, and to find out how Income Audit handles human error regarding minus postings by the cashier food section. and beverage at Aston Bogor Hotel & Resort. The results of the review show that the procedure for checking daily food and beverage income by Income Audit at Aston Bogor Hotel & Resort has gone very well, because it complies with the regulations set by the management. As well as departments and sections related to checking daily food and beverage income by Income Audit at Aston Hotel Bogor & Resort have also carried out their duties in accordance with procedures. Keywords: Income Audit, Food and Beverage Daily Income Check.